The Role of Corporates in Governing Carbon Dioxide Removal: Outlining a Research Agenda - Battersby, Francesca; Heap, Richard J.; Gray, Adam C.; Workman, Mark; Strivens, Finn (Frontiers in Climate, 2022)
With 1500 companies now estimated to have set net zero targets, corporate engagement with carbon dioxide removal (CDR) has gained substantial momentum. Yet despite the corporate sector becoming a key domain of CDR decision-making, corporates have not received research attention as influential actors in the governance of CDR. This paper provides a perspective on how corporates influence and enact de facto governance of CDR. We collate a preliminary evidence base regarding possible modes of CDR governance by corporates. Focusing on voluntary corporate engagement with CDR, we examine how and why firm-level decision-making takes place, and interrogate the implications and impacts of such activity. We find that the current literature focuses on techno-economic attributes of CDR solutions as drivers of corporate engagement; however, the ability for corporates to formulate a (business) case for engaging with CDR is potentially shaped by a broad array of financial and non-financial factors that are currently overlooked. This gives corporates the influence to define what and how to govern, an inherently ‘political act’. We finally highlight possible lenses for future research, noting lessons to be drawn from climate justice, anticipatory governance, responsible innovation, and futures literatures. These could provide a deepened understanding of how governance is being shaped by corporates, and its implications. Ultimately, without awareness and oversight of how CDR is being governed in the real world, policy and governance research may not be successful in driving us towards desired net zero futures.